Do students understand the detrimental effects of mind wandering during online learning?. (July 2019) - Was, Christopher A.; Hollis, R. Benjamin; Dunlosky, John
Abstract: Do students understand the potentially detrimental effects of mind wandering as they are watching a lecture online? To answer this question, we combined methods used to assess mind wandering and metacognitive methods used to assess student's judgments of learning. In two studies, college students watched a video lecture from an online course, and while watching it, responded to standard mind wandering prompts. They then judged how well they would perform on a quiz over the material they had just viewed. Analyses focused on answering two specific questions. Would students' judgments be higher when they reported being on-task than when they reported having task-unrelated thoughts? And, would their judgments be higher when they reported being on-task than when they reported having thoughts about whether they understand the material or reported elaborating on it (which we refer to as task-related thoughts )? Across two studies, students' judgments of learning were higher when they reported being on-task than when they reported having task-unrelated thoughts. Judgment magnitude was also greater when students reported task-related thoughts (e.g., assessing their understanding) than task-unrelated thoughts, even though performance did not differ after these two kinds of report. Relevant to instructional applications, students understand that mind wandering may be potentially detrimental to quiz performance, which suggests they may be open to interventions aimed at reducing mind wandering. Highlights: Participants responded to thought probes while watching an online video lecture. After each thought probe, participants provided a judgment of learning regarding the material just prior to the probe. Higher levels of mind wandering were related to lower judgments of learning (JOLs). Participants' JOLs were lower following off-task thoughts as compared to task-related thoughts and on-task thoughts.